2017
DOI: 10.5935/abc.20170095
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Total Antioxidant Capacity and Cardiometabolic Risk in Non-Obese and Clinically Healthy Young Adults

Abstract: BackgroundThe oxidative biomarkers play an important role in the genesis of cardiometabolic risk-related processes.ObjectiveTo investigate the total antioxidant capacity of plasma and its association with cardiometabolic risk in non-obese and clinically healthy young adults.MethodsUniversity students of the state of Sergipe, Brazil, aged between 18 and 25 years, were recruited for this study from May of 2013 and October of 2014. Anthropometric, clinical and biochemical parameters were measured and analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Costa et al [32] did not find any association of TAC with higher levels of body weight, waist circumference, diastolic blood pressure, total cholesterol HDL-C ratio, and lower HDL-C in non-obese clinically healthy young adults, and concluded that this may be due to compensatory mechanisms that get activated in physiological conditions. This viewpoint is supported by other studies [31] where MDA increased but TAC was not affected. This has been attributed to an increase in antioxidant enzymes such as SOD, supporting the hypothesis that homeostatic mechanisms involving the antioxidant enzymes are able to produce sufficient adaptation to keep the total antioxidant levels unaffected in some conditions but not in others.…”
Section: Groupssupporting
confidence: 86%
See 1 more Smart Citation
“…Costa et al [32] did not find any association of TAC with higher levels of body weight, waist circumference, diastolic blood pressure, total cholesterol HDL-C ratio, and lower HDL-C in non-obese clinically healthy young adults, and concluded that this may be due to compensatory mechanisms that get activated in physiological conditions. This viewpoint is supported by other studies [31] where MDA increased but TAC was not affected. This has been attributed to an increase in antioxidant enzymes such as SOD, supporting the hypothesis that homeostatic mechanisms involving the antioxidant enzymes are able to produce sufficient adaptation to keep the total antioxidant levels unaffected in some conditions but not in others.…”
Section: Groupssupporting
confidence: 86%
“…Ravi Kiran et al [28] found a lower TAC in diabetic and MetS respondents, Picu et al [29], found low TAS along with low antioxidant enzymes, suggesting a strong association between T2DM and obesity, insulin resistance and OS, Bakhtiyari et al [30] reported a far greater effect of MetS than age on OS in senior women, as indicated by a strong correlation of high TG and low HDL-C, with MDA and TAC. Hopps et al [31] found significantly lower TAS in MetS non-diabetics but not in diabetic MetS respondents, and like us, they concluded that the evaluation of TAS may be a useful marker in the monitoring of MetS.…”
Section: Groupssupporting
confidence: 58%
“…In several studies, TAC has been introduced as one of the leading indicators of oxidative stress [ 46 , 47 ]. Therefore, this study measured TAC through DPPH and FRAP assays.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Hatice Sezen, regarding the overall antioxidant status, was consistent with this study results. [40] TAC is one of the important indicators of oxidative stress,[41] as it determines the synergistic effect of different antioxidant compounds in the sample. However, TAC does not evaluate all the antioxidant components and the important role of enzymes such as SOD, CAT, and GPX; consequently, the data should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%